Recovering population of the southern sea otter suppresses a global marine invader - Rikke Jeppesen; Catherine E. de Rivera; Edwin D. Grosholz; M. Tim Tinker; Brent B. Hughes; Ron Eby; Kerstin Wasson (Biological Invasions, 2025)
Understanding the role of apex predators on ecosystems is essential for designing effective conservation strategies. Supporting recovery of apex predators can have many benefits; one that has been rarely examined is control of invasive prey. We investigated whether a recovering apex predator, the southern sea otter ( Enhydra lutris nereis ), can exert local control over a global marine invader, the green crab ( Carcinus maenas ). We determined that southern sea otters in Elkhorn Slough estuary in California can consume large numbers of invasive green crabs and found strong negative relationships in space and time between otter and green crab abundance. Green crabs persisted at highest abundance in this estuary at sites with artificial tidal restriction that were not accessible to otters. Green crab abundance remained lower in this estuary than in all other estuaries in the region, which lack resident sea otters. Conservation organizations and agencies have invested heavily in recovery of southern sea otters, increasing their numbers in this estuary. Restoration of natural tidal exchange, lost marshes, and seagrass beds further support sea otter populations. We have demonstrated that these investments in top predator recovery and habitat restoration have reduced the impacts of a global invader. Our investigation highlights that investment in recovery of top predators can increase beneficial food web interactions and resilience of the entire ecosystem.

Modeling coupled dynamics of an empirical predator-prey system to predict top predator recovery - Samantha N.M. Hamilton; M. Tim Tinker; Joseph Jackson; Joseph A. Tomoleoni; Michael C. Kenner; Julie L. Yee; Tom W. Bell; Max C.N. Castorani; Benjamin H. Becker; Brent B. Hughes (Biological Conservation, 2024)

Environmental, behavioral, and design-related factors affect accuracy and precision of beluga abundance estimates from aerial surveys - Véronique Lesage; Sara Wing; Alain F. Zuur; Jean-François Gosselin; M. Tim Tinker; Arnaud Mosnier; Anne P. St-Pierre; Robert Michaud; Dominique Berteaux (Frontiers in Marine Science, 2024)
Abundance estimation of wildlife populations is frequently derived from systematic survey data. Accuracy and precision of estimates, however, depend on the number of replicate surveys, and on adjustments made for animals unavailable to (availability bias), or available but undetected (perception bias) by observers. This study offers a comprehensive analysis of the relative influence of methodological, environmental and behavioral factors on availability bias estimates from photographic and visual aerial surveys of a small cetacean with a highly clumped distribution, the beluga ( Delphinapterus leucas ). It also estimates the effect of the number of surveys on accuracy and precision of abundance estimates, using 28 replicate visual surveys flown within a 16—29 day window depending on survey year. Availability bias was estimated using detailed dive data from 27 beluga from the St. Lawrence Estuary, Canada, and applied to systematic visual and photographic aerial surveys of this population, flown using various survey platforms. Dive and surface interval durations varied among individuals, and averaged (weighted) 176.6 s (weighted s.e. = 12.6 s) and 51.6 s (weighted s.e. = 4.5 s), respectively. Dive time and instantaneous availability, but not surface time, were affected by local turbidity, seafloor depth, whale behavior (i.e., whether beluga were likely in transit or not), and latent processes that were habitat-specific. Overall, adjustments of availability for these effects remained minor compared to effects from survey design (photographic or visual) and type of platform, and observer search patterns. For instance, mean availability varied from 0.33—0.38 among photographic surveys depending on sightings distribution across the study area, but exceeded 0.40 for all visual surveys. Availability also varied considerably depending on whether observers searched within 0-90° (0.42—0.60) or 170° (0.70—0.80). Simulation-based power analysis indicates a large benefit associated with conducting more than 1 or 2 survey reps, but a declining benefit of conducting > 5—10 survey reps. An increase in sample size from 2, to 5, and 10 reps decreased the CV from 30, to 19 and 13%, respectively, and increased the probability of the abundance estimate being within 15% of true abundance from 0.42, to 0.59 and 0.69 in species like beluga.

Alternations in the foraging behaviour of a primary consumer drive patch transition dynamics in a temperate rocky reef ecosystem - Joshua G. Smith; M. Tim Tinker (Ecology Letters, 2022)
Understanding the role of animal behaviour in linking individuals to ecosystems is central to advancing knowledge surrounding community structure, stability and transition dynamics. Using 22 years of long‐term subtidal monitoring, we show that an abrupt outbreak of purple sea urchins ( Strongylocentrotus purpuratus ), which occurred in 2014 in southern Monterey Bay, California, USA, was primarily driven by a behavioural shift, not by a demographic response (i.e. survival or recruitment). We then tracked the foraging behaviour of sea urchins for 3 years following the 2014 outbreak and found that behaviour is strongly associated with patch state (forest or barren) transition dynamics. Finally, in 2019, we observed a remarkable recovery of kelp forests at a deep rocky reef. We show that this recovery was associated with sea urchin movement from the deep reef to shallow water. These results demonstrate how changes in grazer behaviour can facilitate patch dynamics and dramatically restructure communities and ecosystems.

Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris - Shawn Larson; Roderick B. Gagne; Jim Bodkin; Michael J. Murray; Katherine Ralls; Lizabeth Bowen; Raphael Leblois; Sylvain Piry; Maria Cecilia Penedo; M. Tim Tinker; Holly B. Ernest (Marine Mammal Science, 2021)
Sea otters, Enhydra lutris , were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, population structure, and connectivity between remnant and reintroduced populations. Average genetic diversity within populations was similar: observed heterozygosity 0.55 and 0.53, expected heterozygosity 0.56 and 0.52, unbiased expected heterozygosity 0.57 and 0.52, for reintroduced and remnant populations, respectively. Sea otter population structure was greatest between the Northern and Southern sea otters with further structuring in Northern sea otters into Western, Central, and Southeast populations (including the reintroduced populations). Migrant analyses suggest the successful reintroductions and growth of remnant groups have enhanced connectivity and gene flow between populations throughout many of the sampled Northern populations. We recommend that future management actions for the Southern sea otter focus on future reintroductions to fill the gap between the California and Washington populations ultimately restoring gene flow to the isolated California population.

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Influence of occupation history and habitat on Washington sea otter diet - Jessica R. Hale; Kristin L. Laidre; M. Tim Tinker; Ronald J. Jameson; Steven J. Jeffries; Shawn E. Larson; James L. Bodkin (Marine Mammal Science, 2019)
Habitat characteristics are primary determinants of nearshore marine communities. However, biological drivers like predation can also be important for community composition. Sea otters ( Enhydra lutris ssp.) are a salient example of a keystone species exerting top‐down control on ecosystem community structure. The translocation and subsequent population growth and range expansion of the northern sea otter ( Enhydra lutris kenyoni ) in Washington State over the last five decades has created a spatio‐temporal gradient in sea otter occupation time and density, and acts as a natural experiment to quantify how sea otter population status and habitat type influence sea otter diet. We collected focal observations of sea otters foraging at sites across the gradient in varying habitat types between 2010 and 2017. We quantified sea otter diet composition and diversity, and long‐term rates of energy gain across the gradient. We found that sea otter diet diversity was positively correlated with cumulative sea otter density, while rate of energy gain was negatively correlated with cumulative density. Additionally, we found that habitat type explained 1.77 times more variance in sea otter diet composition than sea otter cumulative density. Long‐term diet studies can provide a broader picture of sea otter population status in Washington State.

Predicting animal home‐range structure and transitions using a multistate Ornstein‐Uhlenbeck biased random walk - Greg A. Breed; Emily A. Golson; M. Tim Tinker (Ecology, 2017)
The home‐range concept is central in animal ecology and behavior, and numerous mechanistic models have been developed to understand home range formation and maintenance. These mechanistic models usually assume a single, contiguous home range. Here we describe and implement a simple home‐range model that can accommodate multiple home‐range centers, form complex shapes, allow discontinuities in use patterns, and infer how external and internal variables affect movement and use patterns. The model assumes individuals associate with two or more home‐range centers and move among them with some estimable probability. Movement in and around home‐range centers is governed by a two‐dimensional Ornstein‐Uhlenbeck process, while transitions between centers are modeled as a stochastic state‐switching process. We augmented this base model by introducing environmental and demographic covariates that modify transition probabilities between home‐range centers and can be estimated to provide insight into the movement process. We demonstrate the model using telemetry data from sea otters ( Enhydra lutris ) in California. The model was fit using a Bayesian Markov Chain Monte Carlo method, which estimated transition probabilities, as well as unique Ornstein‐Uhlenbeck diffusion and centralizing tendency parameters. Estimated parameters could then be used to simulate movement and space use that was virtually indistinguishable from real data. We used Deviance Information Criterion (DIC) scores to assess model fit and determined that both wind and reproductive status were predictive of transitions between home‐range centers. Females were less likely to move between home‐range centers on windy days, less likely to move between centers when tending pups, and much more likely to move between centers just after weaning a pup. These tendencies are predicted by theoretical movement rules but were not previously known and show that our model can extract meaningful behavioral insight from complex movement data.

Dramatic increase in sea otter mortality from white sharks in California - M. Tim Tinker; Brian B. Hatfield; Michael D. Harris; Jack A. Ames (Marine Mammal Science, 2016)
Although southern sea otters ( Enhydra lutris nereis ) are not considered prey for white sharks ( Carcharodon carcharias ), sharks do nonetheless bite sea otters. We analyzed spatial and temporal trends in shark bites on sea otters in California, assessing the frequency of shark bite wounds in 1,870 carcasses collected since 1985. The proportion of stranded sea otters having shark bites has increased sharply since 2003, and white shark bites now account for >50% of recovered carcasses. The trend was most pronounced in the southern part of the range, from Estero Bay to Point Conception, where shark bite frequency has increased eightfold. Seasonal trends were also evident: most shark‐bitten carcasses are recovered in late summer and fall; however, the period of elevated shark bite frequency has lengthened. The causes of these trends are unclear, but possible contributing factors include increased white shark abundance and/or changes in white shark behavior and distribution. In particular, the spatiotemporal patterns of shark‐bitten sea otters match increases in pinniped populations, and the increased availability of marine mammal prey for white sharks may have led to more sharks spending more time in nearshore waters utilized by both sea otters and pinnipeds.

Concentration and retention of T oxoplasma gondii oocysts by marine snails demonstrate a novel mechanism for transmission of terrestrial zoonotic pathogens in coastal ecosystems - Colin Krusor; Woutrina A. Smith; M. Tim Tinker; Mary Silver; Patricia A. Conrad; Karen Shapiro (Environmental Microbiology, 2015)
Summary The parasite T oxoplasma gondii is an environmentally persistent pathogen that can cause fatal disease in humans, terrestrial warm‐blooded animals and aquatic mammals. Although an association between T . gondii exposure and prey specialization on marine snails was identified in threatened C alifornia sea otters, the ability of kelp‐dwelling snails to transmit terrestrially derived pathogens has not been previously investigated. The objective of this study was to measure concentration and retention of T . gondii by marine snails in laboratory aquaria, and to test for natural T . gondii contamination in field‐collected snails. Following exposure to T . gondii ‐containing seawater, oocysts were detected by microscopy in snail faeces and tissues for 10 and 3 days respectively. Nested polymerase chain reaction was also applied as a method for confirming putative T . gondii oocysts detected in snail faeces and tissues by microscopy. T oxoplasma gondii was not detected in field‐collected snails. Results suggest that turban snails are competent transport hosts for T . gondii . By concentrating oocysts in faecal pellets, snails may facilitate entry of T . gondii into the nearshore marine food web. This novel mechanism also represents a general pathway by which marine transmission of terrestrially derived microorganisms can be mediated via pathogen concentration and retention by benthic invertebrates.

Evaluating potential conservation conflicts between two listed species: sea otters and black abalone - Peter Raimondi; Laura J. Jurgens; M. Tim Tinker (Ecology, 2015)
Population consequences of endangered species interacting as predators and prey have been considered theoretically and legally, but rarely investigated in the field. We examined relationships between spatially variable populations of a predator, the California sea otter, Enhydra lutris nereis , and a prey species, the black abalone, Haliotis cracherodii . Both species are federally listed under the Endangered Species Act and co‐occur along the coast of California. We compared the local abundance and habitat distribution of black abalone at 12 sites with varying densities of sea otters. All of the populations of abalone we examined were in the geographic area currently unaffected by withering disease, which has decimated populations south of the study area. Surprisingly, our findings indicate that sea otter density is positively associated with increased black abalone density. The presence of sea otters also correlated with a shift in black abalone to habitat conferring greater refuge, which could decrease illegal human harvest. These results highlight the need for a multi‐species approach to conservation management of the two species, and demonstrate the importance of using field‐collected data rather than simple trophic assumptions to understand relationships between jointly vulnerable predator and prey populations.

The cost of reproduction: differential resource specialization in female and male California sea otters - Emma A. Elliott Smith; Seth D. Newsome; James A. Estes; M. Tim Tinker (Oecologia, 2015)

Timescales alter the inferred strength and temporal consistency of intraspecific diet specialization - Mark Novak; M. Tim Tinker (Oecologia, 2015)

The interaction of intraspecific competition and habitat on individual diet specialization: a near range-wide examination of sea otters - Seth D. Newsome; M. Tim Tinker; Verena A. Gill; Zachary N. Hoyt; Angela Doroff; Linda Nichol; James L. Bodkin (Oecologia, 2015)

Testing the nutritional-limitation, predator-avoidance, and storm-avoidance hypotheses for restricted sea otter habitat use in the Aleutian Islands, Alaska - Nathan L. Stewart; Brenda Konar; M. Tim Tinker (Oecologia, 2015)

Effects of wildfire on sea otter ( Enhydra lutris ) gene transcript profiles - Lizabeth Bowen; A. Keith Miles; Crystal A. Kolden; Justin A. Saarinen; James L. Bodkin; Michael J. Murray; M. Tim Tinker (Marine Mammal Science, 2015)
Wildfires have been shown to impact terrestrial species over a range of temporal scales. Little is known, however, about the more subtle toxicological effects of wildfires, particularly in downstream marine or downwind locations from the wildfire perimeter. These down‐current effects may be just as substantial as those effects within the perimeter. We used gene transcription technology, a sensitive indicator of immunological perturbation, to study the effects of the 2008 Basin Complex Fire on the California coast on a sentinel marine species, the sea otter ( Enhydra lutris ). We captured sea otters in 2008 (3 mo after the Basin Complex Fire was controlled) and 2009 (15 mo after the Basin Complex Fire was controlled) in the adjacent nearshore environment near Big Sur, California. Gene responses were distinctly different between Big Sur temporal groups, signifying detoxification of PAH s, possible associated response to potential malignant transformation, and suppression of immune function as the primary responses of sea otters to fire in 2008 compared to those captured in 2009. In general, gene transcription patterns in the 2008 sea otters were indicative of molecular reactions to organic exposure, malignant transformation, and decreased ability to respond to pathogens that seemed to consistent with short‐term hydrocarbon exposure.

A multi‐decade time series of kelp forest community structure at San Nicolas Island, California (USA) - Michael C. Kenner; James A. Estes; M. Tim Tinker; James L. Bodkin; Robert K. Cowen; Christopher Harrold; Brian B. Hatfield; Mark Novak; Andrew Rassweiler; Daniel C. Reed (Ecology, 2013)
San Nicolas Island is surrounded by broad areas of shallow subtidal habitat, characterized by dynamic kelp forest communities that undergo dramatic and abrupt shifts in community composition. Although these reefs are fished, the physical isolation of the island means that they receive less impact from human activities than most reefs in Southern California, making San Nicolas an ideal place to evaluate alternative theories about the dynamics of these communities. Here we present monitoring data from seven sampling stations surrounding the island, including data on fish, invertebrate, and algal abundance. These data are unusual among subtidal monitoring data sets in that they combine relatively frequent sampling (twice per year) with an exceptionally long time series (since 1980). Other outstanding qualities of the data set are the high taxonomic resolution captured and the monitoring of permanent quadrats and swaths where the history of the community structure at specific locations has been recorded through time. Finally, the data span a period that includes two of the strongest ENSO events on record, a major shift in the Pacific decadal oscillation, and the reintroduction of sea otters to the island in 1987 after at least 150 years of absence. These events provide opportunities to evaluate the effects of bottom‐up forcing, top‐down control, and physical disturbance on shallow rocky reef communities.

Structure and mechanism of diet specialisation: testing models of individual variation in resource use with sea otters - M. Tim Tinker; Paulo R. Guimarães; Mark Novak; Flavia Maria Darcie Marquitti; James L. Bodkin; Michelle Staedler; Gena Bentall; James A. Estes (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 475–483 Abstract Studies of consumer‐resource interactions suggest that individual diet specialisation is empirically widespread and theoretically important to the organisation and dynamics of populations and communities. We used weighted networks to analyze the resource use by sea otters, testing three alternative models for how individual diet specialisation may arise. As expected, individual specialisation was absent when otter density was low, but increased at high‐otter density. A high‐density emergence of nested resource‐use networks was consistent with the model assuming individuals share preference ranks. However, a density‐dependent emergence of a non‐nested modular network for ‘core’ resources was more consistent with the ‘competitive refuge’ model. Individuals from different diet modules showed predictable variation in rank‐order prey preferences and handling times of core resources, further supporting the competitive refuge model. Our findings support a hierarchical organisation of diet specialisation and suggest individual use of core and marginal resources may be driven by different selective pressures.

Using Ecological Function to Develop Recovery Criteria for Depleted Species: Sea Otters and Kelp Forests in the Aleutian Archipelago - JAMES A. ESTES; M. TIM TINKER; JAMES L. BODKIN (Conservation Biology, 2010)
Recovery criteria for depleted species or populations normally are based on demographic measures, the goal being to maintain enough individuals over a sufficiently large area to assure a socially tolerable risk of future extinction. Such demographically based recovery criteria may be insufficient to restore the functional roles of strongly interacting species. We explored the idea of developing a recovery criterion for sea otters (Enhydra lutris) in the Aleutian archipelago on the basis of their keystone role in kelp forest ecosystems. We surveyed sea otters and rocky reef habitats at 34 island‐time combinations. The system nearly always existed in either a kelp‐dominated or deforested phase state, which was predictable from sea otter density. We used a resampling analysis of these data to show that the phase state at any particular island can be determined at 95% probability of correct classification with information from as few as six sites. When sea otter population status (and thus the phase state of the kelp forest) was allowed to vary randomly among islands, just 15 islands had to be sampled to estimate the true proportion that were kelp dominated (within 10%) with 90% confidence. We conclude that kelp forest phase state is a more appropriate, sensitive, and cost‐effective measure of sea otter recovery than the more traditional demographically based metrics, and we suggest that similar approaches have broad potential utility in establishing recovery criteria for depleted populations of other functionally important species .

Using stable isotopes to investigate individual diet specialization in California sea otters ( Enhydra lutris nereis ) - Seth D. Newsome; M. Tim Tinker; Daniel H. Monson; Olav T. Oftedal; Katherine Ralls; Michelle M. Staedler; Marilyn L. Fogel; James A. Estes (Ecology, 2009)
Differences in diet composition among conspecifics (dietary specialization) have been documented across a broad range of taxonomic groups and habitats, and such variation at the individual level is increasingly recognized as an important component of diversity in trophic interactions. Accurate identification of individual dietary specialization, however, requires longitudinal dietary records that are labor‐intensive and cost‐prohibitive to obtain for many species. Here we explore the use of stable isotopes (δ 13 C and δ 15 N) as a promising technique for detecting and quantifying patterns of individual dietary specialization. Southern sea otters ( Enhydra lutris nereis ) offer a unique opportunity for testing this approach because (1) they consume a wide variety of prey that span multiple trophic levels, habitats, and ecologically defined functional groups; and (2) individual diet specialization can be validated with existing observational data. We analyzed the isotopic composition of sea otter vibrissae ( n = 31) in order to characterize inter‐ and intra‐individual variation in sea otter diets at Monterey Bay, California, USA. At the population level, sea otters showed substantial variation in both δ 13 C and δ 15 N values, occupying nearly all of the “isotopic space” created by the diversity of isotopic signatures of potential prey taxa. Most of the variation in sea otter vibrissae was accounted for by differences between individuals, with much less contributed by within‐individual variation. A majority of sea otters (∼80%) showed relatively little temporal variability in isotopic composition, suggesting that the proportional composition of most individuals' diets is relatively constant over time; a few individuals (∼20%) exhibited a high degree of intra‐vibrissa isotopic variability, suggesting seasonal shifts in diet composition. These results and our interpretation of them were supported by long‐term observational data on the diets of radio‐tagged sea otters from the same population ( n = 23). Our results demonstrate that stable isotopes can provide an efficient tool for measuring individual‐ and population‐level dietary breadth and may be useful for studying populations where longitudinal data on individuals would otherwise be impossible to acquire. This will be critical for examining the causes and consequences of dietary variation within and among consumer populations, thereby improving our understanding of these important ecological and evolutionary processes at the community level.

ATTACKS ON SEA OTTERS BY KILLER WHALES - Brian B. Hatfield; Dennis Marks; M. Tim Tinker; Kellie Nolan; Joshua Peirce (Marine Mammal Science, 1998)

The reproductive behavior and energetics of male gray seals ( Halichoerus grypus ) breeding on a land-fast ice substrate - M. Tim Tinker; K. M. Kovacs; Mike O. Hammill (Behavioral Ecology and Sociobiology, 1995)

The reproductive behavior and energetics of male gray seals (Halichoerus grypus) breeding on a land-fast ice substrate - M. Tim Tinker; Kit M. Kovacs; Mike O. Hammill (Behavioral Ecology and Sociobiology, 1995)